Identification, biotransformation, and neuroprotective potential of the ethanol extract of Alpiniae oxyphyllae fructus in neuroinflammation-related cognitive impairment - Yi, Zirong; Wang, Xinyu; Wang, Lin; Yin, Renfang; Qi, Dongying; Liu, Huan; Chen, Yuxin; Xie, Yamei; Ma, Yuming; Hu, Mengqi; Zhang, Nan; Pan, Yanli; et al. (Frontiers in Pharmacology, 2025)
BackgroundNeuroinflammation is a key pathological mechanism underlying various central nervous system (CNS) disorders. Alpiniae Oxyphyllae Fructus (AOF), the dried fruit of Alpinia oxyphylla, has shown therapeutic potential for these disorders. This study aimed to characterize the chemical constituents, biotransformation profiles, and neuroprotective potential of the ethanol extract of AOF in neuroinflammation-related cognitive impairment.MethodsThe ethanol extract of AOF was analyzed using ultra-performance liquid chromatography coupled with high-resolution mass spectrometry (UPLC-HRMS) and Global Natural Products Social Molecular Networking (GNPS). Sequential metabolism experiments were performed to investigate its dynamic biotransformation and blood–brain barrier (BBB) permeability. Neuroprotective effects of sesquiterpenoid-enriched fractions from AOF (SE-AOF) were evaluated in a lipopolysaccharide (LPS)-induced mouse model of neuroinflammation-associated cognitive impairment.ResultsA total of 108 bioactive compounds were identified from the ethanol extract of AOF. Among them, 34 compounds, mainly sesquiterpenoids, were also detected in the cerebrospinal fluid and brain tissue, indicating BBB penetration. SE-AOF significantly improved cognitive function, reduced inflammatory cytokine levels, and alleviated oxidative stress in plasma and brain tissues of LPS-treated mice.ConclusionThese findings demonstrate that the ethanol extract of AOF exerted neuroprotective effects via its bioactive sesquiterpenoids, providing insights into the therapeutic potential of natural products (NPs) against neuroinflammation-related CNS disorders.